The Effect of Carbon Emission Disclosure on Firm Value: The Moderating Role of Independent Commissioners in Indonesia's Energy Sector, 2022-2024 - S.H.K. Kukuh Yoga P.M; Rosmita Rasyid (Jurnal Indonesia Sosial Sains, 2026)
This quantitative descriptive study examines the effect of carbon emission disclosure on firm value and the moderating role of independent commissioners in energy sector companies listed on the Indonesia Stock Exchange during 2022-2024. Agency theory provides the analytical foundation by viewing disclosure as a mechanism that reduces information asymmetry and independent commissioners as a monitoring mechanism. Carbon disclosure was measured using an 18-item index adapted from Choi et al. (2013), firm value was proxied by Tobin's Q, independent commissioners were measured by their proportion on the board, and firm size was included as a control variable. The initial sample comprised 61 companies and 183 firm-year observations. Six extreme Tobin's Q observations identified using the mean ±3 standard deviations criterion were excluded, resulting in 177 observations from 59 companies. Panel-data regression and moderated regression analysis were estimated using a random-effects model with firm-clustered standard errors. Carbon emission disclosure had a positive and significant effect on firm value (β = 0.6192; p = 0.024). Predictive margins showed that Tobin's Q increased from 1.2836 at low disclosure to 1.4556 at high disclosure, a significant difference of 0.1720. The interaction between disclosure and independent commissioners was positive but insignificant (β = 1.3441; p = 0.549). Thus, disclosure appears to reduce information asymmetry and improve market valuation, while the formal proportion of independent commissioners does not by itself strengthen that relationship.